2004
DOI: 10.1113/jphysiol.2004.069070
|View full text |Cite
|
Sign up to set email alerts
|

Acute nociceptive somatic stimulus sensitizes neurones in the spinal cord to colonic distension in the rat

Abstract: The common co-existence of fibromyalgia and chronic abdominal pain could be due to sensitization of spinal neurones (SNs), as a result of viscero-somatic convergence. The objective of this study is to explore the influence of acute nociceptive somatic stimulation in the form of acid injections, into the ipsilateral somatic receptive field of neurones responsive to colorectal distension (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…At least two independent lines of evidence suggest that such enhanced responsiveness affects different inputs to the same second-order neurons (heterosynaptic facilitation). 1) Direct recording from spinal neurons showed increased responses to somatic stimulation of the site of convergence in animal models of visceral hypersensitivity (45,51). 2) Using paradigms that induce long-term potentiation in the spinal cord, Klein et al (26) showed perceptual changes in humans that support the importance of heterosynaptic facilitation as a mechanism of central sensitization.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At least two independent lines of evidence suggest that such enhanced responsiveness affects different inputs to the same second-order neurons (heterosynaptic facilitation). 1) Direct recording from spinal neurons showed increased responses to somatic stimulation of the site of convergence in animal models of visceral hypersensitivity (45,51). 2) Using paradigms that induce long-term potentiation in the spinal cord, Klein et al (26) showed perceptual changes in humans that support the importance of heterosynaptic facilitation as a mechanism of central sensitization.…”
Section: Discussionmentioning
confidence: 97%
“…But this cross talk goes beyond the two neighboring pelvic organs. Experimentally induced cystitis decreases thresholds to stimulation of the hind paw (viscero-somatic sensitization), and inflammation in the lower extremities causes enhanced responses to colorectal distension (somato-visceral sensitization) (7,36,45). On the basis of these results, we hypothesized that sensitization of colon afferents during inflammation will affect convergent afferent pathways from somatic and visceral structures.…”
mentioning
confidence: 93%
“…4,5 Such findings provide an anatomic basis for how pelvic muscle dysfunction might also result in generalized pelvic pain symptoms, via dorsal horn integration of afferent input. [6][7][8][9] Conversely, extinction of somatic neuroinflammatory triggers may normalize central pain sensitivity, and may explain results from a recent study, where pelvic floor massage alone reduced irritative bladder symptoms in painful bladder syndrome (PBS) patients. 10 Thus, a clear need exists to formally characterize pelvic floor pain dysfunction among both somatic and visceral pelvic pain syndromes.…”
mentioning
confidence: 87%
“…UES contractility, after occurrence, is prolonged in arousal vs. nonarousals. multiple afferent-efferent systems are integrated by virtue of brain stem viscerosomatic convergence phenomena (28,35) resulting in aerodigestive defensive reflexes that maintain aerodigestive safety.…”
Section: Discussionmentioning
confidence: 99%